The influence of treatment compliance, family support on the occurrence of positive Acid-Fast Bacilli (BTA) conversion in pulmonary TB patients - Irwan, Irwan; Katili, Deliyana; Ridha, Nadirah Rasyid (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Pulmonary Tuberculosis is an infectious disease caused by the germ Mycobacterium tuberculosis, which is one of the diseases of the 10 causes of death in the world. Treatment of Pulmonary Tuberculosis is given in two stages: the initial (intensive) and advanced. BTA conversion at the end of intensive phase treatment is one of the indicators to see the progress of TB treatment. Low conversion can harm public health and the achievement of TB control and eradication programs. This study aims to determine the factors related to the conversion of a positive acid-resistant bacillus (BTA) in Pulmonary TB patients in the Tilango Health Center Working Area, Gorontalo Regency. Analytical type of observational research with a cross-sectional approach. The total sample of 22 respondents is patients still undergoing treatment for at least 2 months at the Tilango Health Center. The results showed a relationship between treatment compliance (p=0.031) and Pulmonary TB Positive BTA Conversion. At the same time, family support (p=1,000) and health worker encouragement (p=1,000) were not present with Pulmonary TB Positive BTA Conversion, and the most related factor was treatment compliance (OR=0.079). The conclusion is that there is a relationship between treatment compliance and positive BTA conversion of Pulmonary TB patients.